Biological membranes in EV biogenesis, stability, uptake, and cargo transfer: an ISEV position paper arising from the ISEV membranes and EVs workshop. Issue 1 (1st December 2019) - Russell, Ashley E.; Sneider, Alexandra; Witwer, Kenneth W.; Bergese, Paolo; Bhattacharyya, Suvendra N.; Cocks, Alexander; Cocucci, Emanuele; Erdbrügger, Uta; Falcon-Perez, Juan M.; Freeman, David W.; Gallagher, Thomas M.; Hu, Shuaishuai; et al.
ABSTRACT: Paracrine and endocrine roles have increasingly been ascribed to extracellular vesicles (EVs) generated by multicellular organisms. Central to the biogenesis, content, and function of EVs are their delimiting lipid bilayer membranes. To evaluate research progress on membranes and EVs, the International Society for Extracellular Vesicles (ISEV) conducted a workshop in March 2018 in Baltimore, Maryland, USA, bringing together key opinion leaders and hands-on researchers who were selected on the basis of submitted applications. The workshop was accompanied by two scientific surveys and covered four broad topics: EV biogenesis and release; EV uptake and fusion; technologies and strategies used to study EV membranes; and EV transfer and functional assays. In this ISEV position paper, we synthesize the results of the workshop and the related surveys to outline important outstanding questions about EV membranes and describe areas of consensus. The workshop discussions and survey responses reveal that while much progress has been made in the field, there are still several concepts that divide opinion. Good consensus exists in some areas, including particular aspects of EV biogenesis, uptake and downstream signalling. Areas with little to no consensus include EV storage and stability, as well as whether and how EVs fuse with target cells. Further research is needed in these key areas, as a better understanding of membrane biology will contribute substantially towards advancing the field of extracellular vesicles.